Prognostic Value of Diastolic Dysfunction Derived From D-SPECT in Coronary Artery Disease Patients With Normal Ejection Fraction - Bin Xu (Frontiers in Cardiovascular Medicine, 2021)
Diastolic dysfunction (DD) with normal systolic function has been elucidated to be associated with heart failure and worse prognosis. The recently introduced single photon emission computed tomography (SPECT) with dedicated cardiac cadmium-zinc-telluride (CZT) cameras (D-SPECT) is a novel method to quantitate left ventricular functional parameters. We aimed to evaluate the prognostic value of DD derived from D-SPECT in coronary artery disease (CAD) patients with normal ejection fraction. All CAD patients who underwent D-SPECT and invasive coronary angiography within 3 months were considered. DD was defined as peak filling rate (PFR) <2.1 end diastolic volume (EDV, ml)/s according to the D-SPECT results. Patients were divided into three groups: group 1 (n = 226)—normal PFR; group 2 (n = 67)—ischemia-related DD (abnormal stress PFR and normal rest PFR); and group 3 (n = 106)—rest DD (abnormal rest PFR). The primary clinical endpoint of the present study was a composite of heart failure events (HFE). A total of 399 consecutive CAD patients with normal systolic function undergoing stress D-SPECT were analyzed. The incidence rates of HFE among the three groups were 4.0, 7.5, and 11.3%, respectively. Cox regression analysis showed that the multivariate predictors of HFE were rest PFR, diabetes mellitus, obesity, and old age. DD derived from D-SPECT in CAD patients with normal ejection fraction is predictive of HFE.